The Hydra stem cell system: revisited - Holstein, Thomas W. (Cells & development, 2023)
Cnidarians are >600 million years old and are considered the sister group of Bilateria based on numerous molecular phylogenetic studies. Apart from Hydra, the genomes of all major clades of Cnidaria have been uncovered (e.g. Aurelia, Clytia, Nematostella and Acropora) and they reveal a remarkable completeness of the metazoan genomic toolbox. Of particular interest is Hydra, a model system of aging research, regenerative biology, and stem cell biology. With the knowledge gained from scRNA research, it is now possible to characterize the expression profiles of all cell types with great precision. In functional studies, our picture of the Hydra stem cell biology has changed, and we are in the process of obtaining a clear picture of the homeostasis and properties of the different stem cell populations. Even though Hydra is often compared to plant systems, the new data on germline and regeneration, but also on the dynamics and plasticity of the nervous system, show that Hydra with its simple body plan represents in a nutshell the prototype of an animal with stem cell lineages, whose properties correspond in many ways to Bilateria. This review provides an overview of the four stem cell lineages, the two epithelial lineages that constitute the ectoderm and the endoderm, as well as the multipotent somatic interstitial lineage (MPSC) and the germline stem cell lineage (GSC), also known as the interstitial cells of Hydra.
Online veröffentlicht am 28. April 2023, Artikelversion vom 8. Mai 2023
Gesehen am 12.12.2023